Development of 2D plotter - Athauda, Palleha Athaudagedara Sithira Kavin; Manukid Parnichkun; Bohez, Erik L.J.; Lin, Than (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
The main purpose of robotics engineering and automation systems is to reduce the time wasting and avoiding human beings from hazardous situation. In the modern world people use robots such as do their day to day activates, production lines of factories and etc. the aim of this project is making plotter which can be implement to print designs of ships and machines, plans for buildings and so on.
A capstone project submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering in Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B. Sc.) - Asian Institute of Technology, 2015
Keywords: Automation control; Arduino (Programmable controller)